2011
DOI: 10.1186/1471-2458-11-315
|View full text |Cite
|
Sign up to set email alerts
|

The rise in narghile (shisha, hookah) waterpipe tobacco smoking: A qualitative study of perceptions of smokers and non smokers

Abstract: BackgroundThe prevalence of waterpipe tobacco smoking (WTS) in the Middle East region and worldwide is increasing. There is evidence to indicate both short term and long term health effects of WTS, resulting in the issuance of an advisory note by the World Health Organization.MethodsThis research aimed at gaining an in-depth understanding of the factors contributing to the rise in WTS in Lebanon. Qualitative focus groups (25) and in-depth interviews (9) were conducted with adults in Lebanon in 2007. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
128
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(142 citation statements)
references
References 27 publications
13
128
0
Order By: Relevance
“…In the Lebanese context, however, this finding is particularly important, given the alarming smoking epidemic, mainly water-pipe smoking, that is invading the country since the early 1990s (Saade et al, 2008;Nakkash et al, 2011). Our results show statistically significant differences in smoking severity in cases compared to controls, which is consistent with previous findings (Samanic et al, 2006;WilhelmBenartzi et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…In the Lebanese context, however, this finding is particularly important, given the alarming smoking epidemic, mainly water-pipe smoking, that is invading the country since the early 1990s (Saade et al, 2008;Nakkash et al, 2011). Our results show statistically significant differences in smoking severity in cases compared to controls, which is consistent with previous findings (Samanic et al, 2006;WilhelmBenartzi et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…An unpublished survey among school students have shown that the dokha use among the expatriate students from European, British and other western nationalities (Gulf news, 2012). A similar rapid spread of use of water pipes in the Gulf region has been documented in previous literature (Akl et al, 2011;Nakkash et al, 2011).…”
Section: Prevalencesupporting
confidence: 81%
“…The use of tobacco by the adolescents have been reported to affect the academic performance and influence their social life and health (Nakkash et al, 2011). This review focuses on the prevalence, pattern and health effects of dokha use in the Middle East.…”
Section: Dokha: An Emerging Public Health Issue As a Form Of Tobacco mentioning
confidence: 99%
“…Lower educational status, being between ages 25-64 and being employed predicted a higher risk of tobacco use (17). It is important to note that: 1) the numbers of smokers in Egypt has doubled over the past 15 years (2); 2) smoking prevalence increases with age (18); 3) tobacco use is more common among males that are the less educated and of a lower socioeconomic class (2,19); 4) the most updated epidemiology on shisha smoking in Egypt (2013) indicates that approximately 3.3% of the Egyptian population (6.2% of males and 0.3% of females) use shisha (20); and 5) tobacco smoking is more prevalent among males than females; however, the numbers of females smoking has increased rapidly in the last few years due to increased exposure to western culture and increased numbers of working women (2,21,22).…”
Section: Prevalencementioning
confidence: 99%